A multi-disciplinary approach to studying performance among high-level golfers: physiological and biomechanical aspects - Parker, J. (Halmstad University, 2018)
In competitive golf, the player`s ability to hit the ball a long distance affects the score in a positive way. Swing kinematics is considered an important factor in driver performance; one way of improving swing kinematics is through strength and power training. Subsequently, high-level golfers and their coaches often explore novel ways of increasing the distance of a shot, in particular driver carry distance (CD). This licentiate thesis presents two studies with the overall aim of studying how swing kinematic and physical characteristics are associated with driver performance among intercollegiate golf players. The studies report swing kinematics associated with driver performance (study 1) and the impact of isokinetic rotational training on driver performance and swing kinematic variables (study 2).